2018
DOI: 10.1021/acsami.7b17727
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of High-Sensitivity Skin-Attachable Temperature Sensors with Bioinspired Microstructured Adhesive

Abstract: In this study, we demonstrate the fabrication of a highly sensitive flexible temperature sensor with a bioinspired octopus-mimicking adhesive. A resistor-type temperature sensor consisting of a composite of poly(N-isopropylacrylamide) (pNIPAM)-temperature sensitive hydrogel, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate, and carbon nanotubes exhibits a very high thermal sensitivity of 2.6%·°C between 25 and 40 °C so that the change in skin temperature of 0.5 °C can be accurately detected. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(135 citation statements)
references
References 40 publications
2
132
0
1
Order By: Relevance
“…The muscle‐actuation‐induced pressure difference between the inside and outside of the suckers leads to switchable and conformal adhesion to arbitrary surfaces (Figure c) . Inspired by the adhesive mechanism of cephalopods, there have been recent achievements in biomimetic dry adhesives for medical/clinical patches, skin‐attachable temperature sensors, and transfer‐printing technique . Kim and co‐workers demonstrated a suction‐cup‐inspired dry adhesive system for a smart medical patch, enabling highly sensitive biometric sensing and transdermal drug delivery by combining with stretchable electronics and drug‐including nanoparticles (Figure d) .…”
Section: Biosystem‐inspired Smart Skinsmentioning
confidence: 99%
“…The muscle‐actuation‐induced pressure difference between the inside and outside of the suckers leads to switchable and conformal adhesion to arbitrary surfaces (Figure c) . Inspired by the adhesive mechanism of cephalopods, there have been recent achievements in biomimetic dry adhesives for medical/clinical patches, skin‐attachable temperature sensors, and transfer‐printing technique . Kim and co‐workers demonstrated a suction‐cup‐inspired dry adhesive system for a smart medical patch, enabling highly sensitive biometric sensing and transdermal drug delivery by combining with stretchable electronics and drug‐including nanoparticles (Figure d) .…”
Section: Biosystem‐inspired Smart Skinsmentioning
confidence: 99%
“…Various devices incorporating biologically inspired architectures have recently been demonstrated to achieve high conformity to rough, often hairy and/or wet (e.g., perspiration, oil, and blood) surfaces of human interfaces for long‐term signaling. The architectures include gecko‐inspired nanohairs, insect pad‐like microfibrillars, frog pad‐inspired microchannels, and octopus sucker‐like microcavities . Pang et al reported a flexible pressure sensor with a microhairy interface to demonstrate signal amplification and measurements of the weak jugular venous pulses (JVPs) from a wireless transmitter .…”
Section: Bioelectronics With Bioinspired Adhesive Architecturesmentioning
confidence: 99%
“…While bioelectronics with microstructures have been used to increase detection of signal magnitudes by high conformity, diagnostic devices with bioinspired architectures for adhesion to skin have also drawn much attention. Patch‐type sensors with bioinspired dry adhesive architectures provide not only repetitive and long‐term attachment, but also stability for biosignal monitoring without conventional acrylic‐based glues or surgical suture . Kim et al proposed stretchable and conductive adhesives with mushroom‐shaped architectures to demonstrate cost‐effective and reusable all‐in‐one devices for biosignal measurements under active motions (i.e., moving, wrist‐curling, and writing) .…”
Section: Bioelectronics With Bioinspired Adhesive Architecturesmentioning
confidence: 99%
“…Next, we focus on improving its thermal sensitivity. As reported before, doping of PEDOT: PSS with other temperature-sensitive materials such as graphene (Trung et al, 2014(Trung et al, , 2016(Trung et al, , 2018 can further increase its response to temperature (Honda et al, 2014;Oh et al, 2018). Here, we applied the graphene doping strategy to further adjust the temperature sensitivity of PEDOT: PSS nanowires.…”
Section: Doping Effectmentioning
confidence: 92%
“…The thermosensitive mechanism of PEDOT: PSS can be explained by the structural change of PEDOT: PSS induced by the temperature change which eventually alters the conductivity of PEDOT: PSS (Takano et al, 2012;Zhou et al, 2014;Vuorinen et al, 2016). Previous studies on PEDOT: PSS based temperature sensors were focused on doping the PEDOT: PSS with other materials to enhance the device's response to temperature (Honda et al, 2014;Oh et al, 2018). However, understanding the control parameters regarding their response time to temperature change is less covered.…”
Section: Introductionmentioning
confidence: 99%